Non-parametric methods for quantifying the Allee effect among cancer cell populations - Källsgård, Anna (My University, 2023)
The Allee effect is a phenomenon that has been extensively studied in ecology and is characterized by the per-capita growth rate of a population being low, zero, or even negative in small populations. Recent studies have shown the effect being present within human cancer cell populations. This thesis formulates two non-parametric methods to quantify the Allee effect among cancer cell populations. An agentbased model for cell population dynamics was formulated and used to generate simulated datasets, and microscopic images of cervical cancer cells constitute an in vitro dataset. Promising results were achieved for large simulated datasets. The in vitro dataset considered for this thesis was not of sufficient size for reliable inference, implying the need for large, high-quality datasets for future studies.